The Star newspaper: Abbreviation strategies in SMS column / Caroline Joseph and Rosita Aminullah - Joseph, Caroline; Aminullah, Rosita (2012)
The advancement of technology has influenced the held of language greatly. In the beginning, we have witnessed how the English language has been experiencing revolution with abbreviations and short forms that were being widely used in the Internet via e-mails. Today, the technology of SMS that is offered by mobile phones is also beginning to bring about some changes in the English language as far as the informal language is concerned Thus, this research is a study of the creative strategies of abbreviations that are found in the SMS column that is printed in The Star newspaper. This study looks into randomly selected SMS texts that are published in The Star newspaper and the research intends to look into creative abbreviation strategies in the SMS texts. The findings show that although The Star newspaper publishes its print in Standard English, in order .to be at par with the latest technology, the newspaper has allowed the use of abbreviations use in the SMS column for its readers to share their views.